Conservation of 87Sr/86Sr isotopic ratios during the winemaking processes of 'Red' wines to validate their use as geographic tracer. (1st January 2016) - Marchionni, Sara; Buccianti, Antonella; Bollati, Andrea; Braschi, Eleonora; Cifelli, Francesca; Molin, Paola; Parotto, Maurizio; Mattei, Massimo; Tommasini, Simone; Conticelli, Sandro
Highlights: Sr isotopes are a robust fingerprint to trace the geographic authenticity of wine. Sr isotopes are not contaminated during the winemaking processes. Wine has constant 87 Sr/ 86 Sr composition independent of vintage year. 87 Sr/ 86 Sr of the bioavailable soil solutions is related to geological substratum. The bioavailable soil solution fraction transfers its isotopic signature to wine. Abstract: 87 Sr/ 86 Sr has been determined in wines, musts grape juices, soils and rocks from six selected vineyards of 'Cesanese' wine area. Cesanese is a monocultivar wine from a small region characterised by different geologic substrata, a key locality to test the influence of both substratum and winemaking procedure on the 87 Sr/ 86 Sr of wines. Experimental work has been performed on wines from different vintage years to check possible seasonal variations. The data reveal that 87 Sr/ 86 Sr does not change through time, to validate the selection of wineries performed, and in addition no isotopic variations are observed during winemaking. Indeed, no significant isotopic variations have been observed in musts and wines. These findings reinforce the hypothesis that the isotopic signature of wines is strongly related to the bioavailable fraction of the soil rather than to its bulk. The data corroborate the possibility that Sr-isotopes of high-quality wines can be used as a reliable tool for fingerprinting wine geographic provenance.